PENGELOLAAN PELAKSANAAN SHOLAT FARDHU MELALUI PENDEKATAN METODE RESITASI PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Sujiyono Ps Sujiyono Ps (Manajer Pendididikan, 2015)
The purposes of research to know the management of fardhu prayer trought the method of resitasi. The lessons of the Islamic religious education is not enough just to be mastered, but it isnecessary to be applied in the attitudes and behaviorin a student’s life everyday. This study carried out by using research a class action, in a class to know as a result of actions implemented on asubject of research in the class. The result of this research is the use of methods resitasi in improving the implementation management of the fardhu prayer to a positif effect on students.Keyword: management, prayer fardhu, islamic religious, education.